Evidence for two kinds of hydrogen-bonding networks in ionic solutions by 2D infrared correlation spectroscopy - Daitaro Ishikawa; Anqi He; Yizhuang Xu; Tomoyuki Fujii; Yukihiro Ozaki (Scientific Reports)
Abstract IR spectra from 4000 to 100 cm–1 were measured for four kinds of alkali chloride solutions (LiCl, NaCl, KCl, CsCl solutions) with different concentrations. Their second derivative spectra revealed two bands around 3400 and 3160 cm–1 attributed to the OH stretching mode of weakly hydrogen-bonded (WHB) and strongly hydrogen-bonded (SHB) water species, respectively. Two-dimensional correlation spectroscopy (2D-COS) was applied to analyze the IR spectra. Two autopeaks in a 2D synchronous spectrum correspond to the WHB and SHB bands, respectively. Moreover, 2D-COS confirmed the existence of two bands around 700 and 350 cm–1 in the 1000 –100 cm–1 region. The bands at 700 and 350 cm–1 are assignable to liberational L2 modes and correlated with SHB (~ 3160 cm–1) and WHB band (~ 3400 cm–1), respectively, revealed by the hetero 2D-COS spectrum. These results suggest the two kinds of hydrogen-bonding networks are constructed by SHB or WHB water species in the alkali chloride solutions.